# mathlibdocumentation

algebra.ordered_group

# Ordered groups #

This file develops the basics of ordered groups.

## Implementation details #

Unfortunately, the number of ' appended to lemmas in this file may differ between the multiplicative and the additive version of a lemma. The reason is that we did not want to change existing names in the library.

@[instance]
@[class]
structure ordered_add_comm_group (α : Type u) :
Type u
• add : α → α → α
• add_assoc : ∀ (a b c_1 : α), a + b + c_1 = a + (b + c_1)
• zero : α
• zero_add : ∀ (a : α), 0 + a = a
• add_zero : ∀ (a : α), a + 0 = a
• nsmul : α → α
• nsmul_zero' : (∀ (x : α), . "try_refl_tac"
• nsmul_succ' : (∀ (n : ) (x : α), . "try_refl_tac"
• neg : α → α
• sub : α → α → α
• sub_eq_add_neg : (∀ (a b : α), a - b = a + -b) . "try_refl_tac"
• add_left_neg : ∀ (a : α), -a + a = 0
• add_comm : ∀ (a b : α), a + b = b + a
• le : α → α → Prop
• lt : α → α → Prop
• le_refl : ∀ (a : α), a a
• le_trans : ∀ (a b c_1 : α), a bb c_1a c_1
• lt_iff_le_not_le : (∀ (a b : α), a < b a b ¬b a) . "order_laws_tac"
• le_antisymm : ∀ (a b : α), a bb aa = b
• add_le_add_left : ∀ (a b : α), a b∀ (c_1 : α), c_1 + a c_1 + b

An ordered additive commutative group is an additive commutative group with a partial order in which addition is strictly monotone.

Instances
@[instance]
@[instance]
@[class]
structure ordered_comm_group (α : Type u) :
Type u
• mul : α → α → α
• mul_assoc : ∀ (a b c_1 : α), (a * b) * c_1 = a * b * c_1
• one : α
• one_mul : ∀ (a : α), 1 * a = a
• mul_one : ∀ (a : α), a * 1 = a
• npow : α → α
• npow_zero' : (∀ (x : α), = 1) . "try_refl_tac"
• npow_succ' : (∀ (n : ) (x : α), = x * . "try_refl_tac"
• inv : α → α
• div : α → α → α
• div_eq_mul_inv : (∀ (a b : α), a / b = a * b⁻¹) . "try_refl_tac"
• mul_left_inv : ∀ (a : α), a⁻¹ * a = 1
• mul_comm : ∀ (a b : α), a * b = b * a
• le : α → α → Prop
• lt : α → α → Prop
• le_refl : ∀ (a : α), a a
• le_trans : ∀ (a b c_1 : α), a bb c_1a c_1
• lt_iff_le_not_le : (∀ (a b : α), a < b a b ¬b a) . "order_laws_tac"
• le_antisymm : ∀ (a b : α), a bb aa = b
• mul_le_mul_left : ∀ (a b : α), a b∀ (c_1 : α), c_1 * a c_1 * b

An ordered commutative group is an commutative group with a partial order in which multiplication is strictly monotone.

Instances
@[instance]
@[instance]
@[instance]
def units.ordered_comm_group {α : Type u}  :

The units of an ordered commutative monoid form an ordered commutative group.

Equations
theorem ordered_comm_group.mul_lt_mul_left' {α : Type u} (a b : α) (h : a < b) (c : α) :
c * a < c * b
theorem ordered_add_comm_group.add_lt_add_left {α : Type u} (a b : α) (h : a < b) (c : α) :
c + a < c + b
theorem ordered_add_comm_group.le_of_add_le_add_left {α : Type u} {a b c : α} (h : a + b a + c) :
b c
theorem ordered_comm_group.le_of_mul_le_mul_left {α : Type u} {a b c : α} (h : a * b a * c) :
b c
theorem ordered_comm_group.lt_of_mul_lt_mul_left {α : Type u} {a b c : α} (h : a * b < a * c) :
b < c
theorem ordered_add_comm_group.lt_of_add_lt_add_left {α : Type u} {a b c : α} (h : a + b < a + c) :
b < c
@[instance]
@[instance]
Equations
@[instance]
@[instance]
theorem neg_le_neg {α : Type u} {a b : α} (h : a b) :
-b -a
theorem inv_le_inv' {α : Type u} {a b : α} (h : a b) :
theorem le_of_neg_le_neg {α : Type u} {a b : α} (h : -b -a) :
a b
theorem le_of_inv_le_inv {α : Type u} {a b : α} (h : b⁻¹ a⁻¹) :
a b
theorem one_le_of_inv_le_one {α : Type u} {a : α} (h : a⁻¹ 1) :
1 a
theorem nonneg_of_neg_nonpos {α : Type u} {a : α} (h : -a 0) :
0 a
theorem inv_le_one_of_one_le {α : Type u} {a : α} (h : 1 a) :
theorem neg_nonpos_of_nonneg {α : Type u} {a : α} (h : 0 a) :
-a 0
theorem le_one_of_one_le_inv {α : Type u} {a : α} (h : 1 a⁻¹) :
a 1
theorem nonpos_of_neg_nonneg {α : Type u} {a : α} (h : 0 -a) :
a 0
theorem one_le_inv_of_le_one {α : Type u} {a : α} (h : a 1) :
theorem neg_nonneg_of_nonpos {α : Type u} {a : α} (h : a 0) :
0 -a
theorem neg_lt_neg {α : Type u} {a b : α} (h : a < b) :
-b < -a
theorem inv_lt_inv' {α : Type u} {a b : α} (h : a < b) :
theorem lt_of_inv_lt_inv {α : Type u} {a b : α} (h : b⁻¹ < a⁻¹) :
a < b
theorem lt_of_neg_lt_neg {α : Type u} {a b : α} (h : -b < -a) :
a < b
theorem pos_of_neg_neg {α : Type u} {a : α} (h : -a < 0) :
0 < a
theorem one_lt_of_inv_inv {α : Type u} {a : α} (h : a⁻¹ < 1) :
1 < a
theorem inv_inv_of_one_lt {α : Type u} {a : α} (h : 1 < a) :
a⁻¹ < 1
theorem neg_neg_of_pos {α : Type u} {a : α} (h : 0 < a) :
-a < 0
theorem neg_of_neg_pos {α : Type u} {a : α} (h : 0 < -a) :
a < 0
theorem inv_of_one_lt_inv {α : Type u} {a : α} (h : 1 < a⁻¹) :
a < 1
theorem one_lt_inv_of_inv {α : Type u} {a : α} (h : a < 1) :
1 < a⁻¹
theorem neg_pos_of_neg {α : Type u} {a : α} (h : a < 0) :
0 < -a
theorem le_neg_of_le_neg {α : Type u} {a b : α} (h : a -b) :
b -a
theorem le_inv_of_le_inv {α : Type u} {a b : α} (h : a b⁻¹) :
theorem inv_le_of_inv_le {α : Type u} {a b : α} (h : a⁻¹ b) :
theorem neg_le_of_neg_le {α : Type u} {a b : α} (h : -a b) :
-b a
theorem lt_neg_of_lt_neg {α : Type u} {a b : α} (h : a < -b) :
b < -a
theorem lt_inv_of_lt_inv {α : Type u} {a b : α} (h : a < b⁻¹) :
b < a⁻¹
theorem inv_lt_of_inv_lt {α : Type u} {a b : α} (h : a⁻¹ < b) :
b⁻¹ < a
theorem neg_lt_of_neg_lt {α : Type u} {a b : α} (h : -a < b) :
-b < a
theorem add_le_of_le_neg_add {α : Type u} {a b c : α} (h : b -a + c) :
a + b c
theorem mul_le_of_le_inv_mul {α : Type u} {a b c : α} (h : b a⁻¹ * c) :
a * b c
theorem le_inv_mul_of_mul_le {α : Type u} {a b c : α} (h : a * b c) :
b a⁻¹ * c
theorem le_neg_add_of_add_le {α : Type u} {a b c : α} (h : a + b c) :
b -a + c
theorem le_mul_of_inv_mul_le {α : Type u} {a b c : α} (h : b⁻¹ * a c) :
a b * c
theorem le_add_of_neg_add_le {α : Type u} {a b c : α} (h : -b + a c) :
a b + c
theorem neg_add_le_of_le_add {α : Type u} {a b c : α} (h : a b + c) :
-b + a c
theorem inv_mul_le_of_le_mul {α : Type u} {a b c : α} (h : a b * c) :
b⁻¹ * a c
theorem le_mul_of_inv_mul_le_left {α : Type u} {a b c : α} (h : b⁻¹ * a c) :
a b * c
theorem le_add_of_neg_add_le_left {α : Type u} {a b c : α} (h : -b + a c) :
a b + c
theorem neg_add_le_left_of_le_add {α : Type u} {a b c : α} (h : a b + c) :
-b + a c
theorem inv_mul_le_left_of_le_mul {α : Type u} {a b c : α} (h : a b * c) :
b⁻¹ * a c
theorem le_mul_of_inv_mul_le_right {α : Type u} {a b c : α} (h : c⁻¹ * a b) :
a b * c
theorem le_add_of_neg_add_le_right {α : Type u} {a b c : α} (h : -c + a b) :
a b + c
theorem neg_add_le_right_of_le_add {α : Type u} {a b c : α} (h : a b + c) :
-c + a b
theorem inv_mul_le_right_of_le_mul {α : Type u} {a b c : α} (h : a b * c) :
c⁻¹ * a b
theorem add_lt_of_lt_neg_add {α : Type u} {a b c : α} (h : b < -a + c) :
a + b < c
theorem mul_lt_of_lt_inv_mul {α : Type u} {a b c : α} (h : b < a⁻¹ * c) :
a * b < c
theorem lt_inv_mul_of_mul_lt {α : Type u} {a b c : α} (h : a * b < c) :
b < a⁻¹ * c
theorem lt_neg_add_of_add_lt {α : Type u} {a b c : α} (h : a + b < c) :
b < -a + c
theorem lt_add_of_neg_add_lt {α : Type u} {a b c : α} (h : -b + a < c) :
a < b + c
theorem lt_mul_of_inv_mul_lt {α : Type u} {a b c : α} (h : b⁻¹ * a < c) :
a < b * c
theorem neg_add_lt_of_lt_add {α : Type u} {a b c : α} (h : a < b + c) :
-b + a < c
theorem inv_mul_lt_of_lt_mul {α : Type u} {a b c : α} (h : a < b * c) :
b⁻¹ * a < c
theorem lt_add_of_neg_add_lt_left {α : Type u} {a b c : α} (h : -b + a < c) :
a < b + c
theorem lt_mul_of_inv_mul_lt_left {α : Type u} {a b c : α} (h : b⁻¹ * a < c) :
a < b * c
theorem inv_mul_lt_left_of_lt_mul {α : Type u} {a b c : α} (h : a < b * c) :
b⁻¹ * a < c
theorem neg_add_lt_left_of_lt_add {α : Type u} {a b c : α} (h : a < b + c) :
-b + a < c
theorem lt_add_of_neg_add_lt_right {α : Type u} {a b c : α} (h : -c + a < b) :
a < b + c
theorem lt_mul_of_inv_mul_lt_right {α : Type u} {a b c : α} (h : c⁻¹ * a < b) :
a < b * c
theorem inv_mul_lt_right_of_lt_mul {α : Type u} {a b c : α} (h : a < b * c) :
c⁻¹ * a < b
theorem neg_add_lt_right_of_lt_add {α : Type u} {a b c : α} (h : a < b + c) :
-c + a < b
@[simp]
theorem inv_lt_one_iff_one_lt {α : Type u} {a : α} :
a⁻¹ < 1 1 < a
@[simp]
theorem neg_neg_iff_pos {α : Type u} {a : α} :
-a < 0 0 < a
@[simp]
theorem neg_le_neg_iff {α : Type u} {a b : α} :
-a -b b a
@[simp]
theorem inv_le_inv_iff {α : Type u} {a b : α} :
theorem neg_le {α : Type u} {a b : α} :
-a b -b a
theorem inv_le' {α : Type u} {a b : α} :
theorem le_neg {α : Type u} {a b : α} :
a -b b -a
theorem le_inv' {α : Type u} {a b : α} :
theorem inv_le_iff_one_le_mul {α : Type u} {a b : α} :
a⁻¹ b 1 b * a
theorem neg_le_iff_add_nonneg {α : Type u} {a b : α} :
-a b 0 b + a
theorem inv_le_iff_one_le_mul' {α : Type u} {a b : α} :
a⁻¹ b 1 a * b
theorem neg_le_iff_add_nonneg' {α : Type u} {a b : α} :
-a b 0 a + b
theorem neg_lt_iff_pos_add {α : Type u} {a b : α} :
-a < b 0 < b + a
theorem inv_lt_iff_one_lt_mul {α : Type u} {a b : α} :
a⁻¹ < b 1 < b * a
theorem inv_lt_iff_one_lt_mul' {α : Type u} {a b : α} :
a⁻¹ < b 1 < a * b
theorem neg_lt_iff_pos_add' {α : Type u} {a b : α} :
-a < b 0 < a + b
theorem le_neg_iff_add_nonpos {α : Type u} {a b : α} :
a -b a + b 0
theorem le_inv_iff_mul_le_one {α : Type u} {a b : α} :
a b⁻¹ a * b 1
theorem le_inv_iff_mul_le_one' {α : Type u} {a b : α} :
a b⁻¹ b * a 1
theorem le_neg_iff_add_nonpos' {α : Type u} {a b : α} :
a -b b + a 0
theorem lt_inv_iff_mul_lt_one {α : Type u} {a b : α} :
a < b⁻¹ a * b < 1
theorem lt_neg_iff_add_neg {α : Type u} {a b : α} :
a < -b a + b < 0
theorem lt_inv_iff_mul_lt_one' {α : Type u} {a b : α} :
a < b⁻¹ b * a < 1
theorem lt_neg_iff_add_neg' {α : Type u} {a b : α} :
a < -b b + a < 0
@[simp]
theorem neg_nonpos {α : Type u} {a : α} :
-a 0 0 a
@[simp]
theorem inv_le_one' {α : Type u} {a : α} :
a⁻¹ 1 1 a
@[simp]
theorem one_le_inv' {α : Type u} {a : α} :
1 a⁻¹ a 1
@[simp]
theorem neg_nonneg {α : Type u} {a : α} :
0 -a a 0
theorem inv_le_self {α : Type u} {a : α} (h : 1 a) :
theorem neg_le_self {α : Type u} {a : α} (h : 0 a) :
-a a
theorem self_le_inv {α : Type u} {a : α} (h : a 1) :
theorem self_le_neg {α : Type u} {a : α} (h : a 0) :
a -a
@[simp]
theorem inv_lt_inv_iff {α : Type u} {a b : α} :
a⁻¹ < b⁻¹ b < a
@[simp]
theorem neg_lt_neg_iff {α : Type u} {a b : α} :
-a < -b b < a
theorem inv_lt_one' {α : Type u} {a : α} :
a⁻¹ < 1 1 < a
theorem neg_lt_zero {α : Type u} {a : α} :
-a < 0 0 < a
theorem neg_pos {α : Type u} {a : α} :
0 < -a a < 0
theorem one_lt_inv' {α : Type u} {a : α} :
1 < a⁻¹ a < 1
theorem neg_lt {α : Type u} {a b : α} :
-a < b -b < a
theorem inv_lt' {α : Type u} {a b : α} :
a⁻¹ < b b⁻¹ < a
theorem lt_inv' {α : Type u} {a b : α} :
a < b⁻¹ b < a⁻¹
theorem lt_neg {α : Type u} {a b : α} :
a < -b b < -a
theorem neg_lt_self {α : Type u} {a : α} (h : 0 < a) :
-a < a
theorem inv_lt_self {α : Type u} {a : α} (h : 1 < a) :
a⁻¹ < a
theorem le_neg_add_iff_add_le {α : Type u} {a b c : α} :
b -a + c a + b c
theorem le_inv_mul_iff_mul_le {α : Type u} {a b c : α} :
b a⁻¹ * c a * b c
@[simp]
theorem inv_mul_le_iff_le_mul {α : Type u} {a b c : α} :
b⁻¹ * a c a b * c
@[simp]
theorem neg_add_le_iff_le_add {α : Type u} {a b c : α} :
-b + a c a b + c
theorem mul_inv_le_iff_le_mul {α : Type u} {a b c : α} :
a * c⁻¹ b a b * c
theorem add_neg_le_iff_le_add {α : Type u} {a b c : α} :
a + -c b a b + c
@[simp]
theorem mul_inv_le_iff_le_mul' {α : Type u} {a b c : α} :
a * b⁻¹ c a b * c
@[simp]
theorem add_neg_le_iff_le_add' {α : Type u} {a b c : α} :
a + -b c a b + c
theorem inv_mul_le_iff_le_mul' {α : Type u} {a b c : α} :
c⁻¹ * a b a b * c
theorem neg_add_le_iff_le_add' {α : Type u} {a b c : α} :
-c + a b a b + c
@[simp]
theorem lt_inv_mul_iff_mul_lt {α : Type u} {a b c : α} :
b < a⁻¹ * c a * b < c
@[simp]
theorem lt_neg_add_iff_add_lt {α : Type u} {a b c : α} :
b < -a + c a + b < c
@[simp]
theorem inv_mul_lt_iff_lt_mul {α : Type u} {a b c : α} :
b⁻¹ * a < c a < b * c
@[simp]
theorem neg_add_lt_iff_lt_add {α : Type u} {a b c : α} :
-b + a < c a < b + c
theorem neg_add_lt_iff_lt_add_right {α : Type u} {a b c : α} :
-c + a < b a < b + c
theorem inv_mul_lt_iff_lt_mul_right {α : Type u} {a b c : α} :
c⁻¹ * a < b a < b * c
theorem div_le_div_iff' {α : Type u} {a b c d : α} :
a * b⁻¹ c * d⁻¹ a * d c * b
theorem add_neg_le_add_neg_iff {α : Type u} {a b c d : α} :
a + -b c + -d a + d c + b
@[simp]
theorem sub_le_self_iff {α : Type u} (a : α) {b : α} :
a - b a 0 b
@[simp]
theorem div_le_self_iff {α : Type u} (a : α) {b : α} :
a / b a 1 b
@[simp]
theorem div_lt_self_iff {α : Type u} (a : α) {b : α} :
a / b < a 1 < b
@[simp]
theorem sub_lt_self_iff {α : Type u} (a : α) {b : α} :
a - b < a 0 < b
def function.injective.ordered_add_comm_group {α : Type u} {β : Type u_1} [has_zero β] [has_add β] [has_neg β] [has_sub β] (f : β → α) (hf : function.injective f) (one : f 0 = 0) (mul : ∀ (x y : β), f (x + y) = f x + f y) (inv : ∀ (x : β), f (-x) = -f x) (div : ∀ (x y : β), f (x - y) = f x - f y) :

Pullback an ordered_add_comm_group under an injective map.

def function.injective.ordered_comm_group {α : Type u} {β : Type u_1} [has_one β] [has_mul β] [has_inv β] [has_div β] (f : β → α) (hf : function.injective f) (one : f 1 = 1) (mul : ∀ (x y : β), f (x * y) = (f x) * f y) (inv : ∀ (x : β), f x⁻¹ = (f x)⁻¹) (div : ∀ (x y : β), f (x / y) = f x / f y) :

Pullback an ordered_comm_group under an injective map.

Equations
theorem sub_le_sub {α : Type u} {a b c d : α} (hab : a b) (hcd : c d) :
a - d b - c
theorem sub_lt_sub {α : Type u} {a b c d : α} (hab : a < b) (hcd : c < d) :
a - d < b - c
theorem sub_le_self {α : Type u} (a : α) {b : α} :
0 ba - b a

Alias of sub_le_self_iff.

theorem sub_lt_self {α : Type u} (a : α) {b : α} :
0 < ba - b < a

Alias of sub_lt_self_iff.

theorem sub_le_sub_iff {α : Type u} {a b c d : α} :
a - b c - d a + d c + b
@[simp]
theorem sub_le_sub_iff_left {α : Type u} (a : α) {b c : α} :
a - b a - c c b
theorem sub_le_sub_left {α : Type u} {a b : α} (h : a b) (c : α) :
c - b c - a
@[simp]
theorem sub_le_sub_iff_right {α : Type u} {a b : α} (c : α) :
a - c b - c a b
theorem sub_le_sub_right {α : Type u} {a b : α} (h : a b) (c : α) :
a - c b - c
@[simp]
theorem sub_lt_sub_iff_left {α : Type u} (a : α) {b c : α} :
a - b < a - c c < b
theorem sub_lt_sub_left {α : Type u} {a b : α} (h : a < b) (c : α) :
c - b < c - a
@[simp]
theorem sub_lt_sub_iff_right {α : Type u} {a b : α} (c : α) :
a - c < b - c a < b
theorem sub_lt_sub_right {α : Type u} {a b : α} (h : a < b) (c : α) :
a - c < b - c
@[simp]
theorem sub_nonneg {α : Type u} {a b : α} :
0 a - b b a
theorem le_of_sub_nonneg {α : Type u} {a b : α} :
0 a - bb a

Alias of sub_nonneg.

theorem sub_nonneg_of_le {α : Type u} {a b : α} :
b a0 a - b

Alias of sub_nonneg.

@[simp]
theorem sub_nonpos {α : Type u} {a b : α} :
a - b 0 a b
theorem sub_nonpos_of_le {α : Type u} {a b : α} :
a ba - b 0

Alias of sub_nonpos.

theorem le_of_sub_nonpos {α : Type u} {a b : α} :
a - b 0a b

Alias of sub_nonpos.

@[simp]
theorem sub_pos {α : Type u} {a b : α} :
0 < a - b b < a
theorem lt_of_sub_pos {α : Type u} {a b : α} :
0 < a - bb < a

Alias of sub_pos.

theorem sub_pos_of_lt {α : Type u} {a b : α} :
b < a0 < a - b

Alias of sub_pos.

@[simp]
theorem sub_lt_zero {α : Type u} {a b : α} :
a - b < 0 a < b
theorem lt_of_sub_neg {α : Type u} {a b : α} :
a - b < 0a < b

Alias of sub_lt_zero.

theorem sub_neg_of_lt {α : Type u} {a b : α} :
a < ba - b < 0

Alias of sub_lt_zero.

theorem le_sub_iff_add_le' {α : Type u} {a b c : α} :
b c - a a + b c
theorem le_sub_iff_add_le {α : Type u} {a b c : α} :
a c - b a + b c
theorem add_le_of_le_sub_right {α : Type u} {a b c : α} :
a c - ba + b c

Alias of le_sub_iff_add_le.

theorem le_sub_right_of_add_le {α : Type u} {a b c : α} :
a + b ca c - b

Alias of le_sub_iff_add_le.

theorem sub_le_iff_le_add' {α : Type u} {a b c : α} :
a - b c a b + c
theorem add_le_of_le_sub_left {α : Type u} {a b c : α} :
b c - aa + b c

Alias of le_sub_iff_add_le'.

theorem le_sub_left_of_add_le {α : Type u} {a b c : α} :
a + b cb c - a

Alias of le_sub_iff_add_le'.

theorem sub_le_iff_le_add {α : Type u} {a b c : α} :
a - c b a b + c
@[simp]
theorem neg_le_sub_iff_le_add {α : Type u} {a b c : α} :
-b a - c c a + b
theorem neg_le_sub_iff_le_add' {α : Type u} {a b c : α} :
-a b - c c a + b
theorem sub_le {α : Type u} {a b c : α} :
a - b c a - c b
theorem le_sub {α : Type u} {a b c : α} :
a b - c c b - a
theorem lt_sub_iff_add_lt' {α : Type u} {a b c : α} :
b < c - a a + b < c
theorem add_lt_of_lt_sub_left {α : Type u} {a b c : α} :
b < c - aa + b < c

Alias of lt_sub_iff_add_lt'.

theorem lt_sub_left_of_add_lt {α : Type u} {a b c : α} :
a + b < cb < c - a

Alias of lt_sub_iff_add_lt'.

theorem lt_sub_iff_add_lt {α : Type u} {a b c : α} :
a < c - b a + b < c
theorem add_lt_of_lt_sub_right {α : Type u} {a b c : α} :
a < c - ba + b < c

Alias of lt_sub_iff_add_lt.

theorem lt_sub_right_of_add_lt {α : Type u} {a b c : α} :
a + b < ca < c - b

Alias of lt_sub_iff_add_lt.

theorem sub_lt_iff_lt_add' {α : Type u} {a b c : α} :
a - b < c a < b + c
theorem sub_left_lt_of_lt_add {α : Type u} {a b c : α} :
a < b + ca - b < c

Alias of sub_lt_iff_lt_add'.

theorem lt_add_of_sub_left_lt {α : Type u} {a b c : α} :
a - b < ca < b + c

Alias of sub_lt_iff_lt_add'.

theorem sub_lt_iff_lt_add {α : Type u} {a b c : α} :
a - c < b a < b + c
theorem lt_add_of_sub_right_lt {α : Type u} {a b c : α} :
a - c < ba < b + c

Alias of sub_lt_iff_lt_add.

theorem sub_right_lt_of_lt_add {α : Type u} {a b c : α} :
a < b + ca - c < b

Alias of sub_lt_iff_lt_add.

@[simp]
theorem neg_lt_sub_iff_lt_add {α : Type u} {a b c : α} :
-b < a - c c < a + b
theorem neg_lt_sub_iff_lt_add' {α : Type u} {a b c : α} :
-a < b - c c < a + b
theorem sub_lt {α : Type u} {a b c : α} :
a - b < c a - c < b
theorem lt_sub {α : Type u} {a b c : α} :
a < b - c c < b - a

### Linearly ordered commutative groups #

@[instance]
@[instance]
@[class]
structure linear_ordered_add_comm_group (α : Type u) :
Type u
• add : α → α → α
• add_assoc : ∀ (a b c_1 : α), a + b + c_1 = a + (b + c_1)
• zero : α
• zero_add : ∀ (a : α), 0 + a = a
• add_zero : ∀ (a : α), a + 0 = a
• nsmul : α → α
• nsmul_zero' : (∀ (x : α), . "try_refl_tac"
• nsmul_succ' : (∀ (n : ) (x : α), . "try_refl_tac"
• neg : α → α
• sub : α → α → α
• sub_eq_add_neg : (∀ (a b : α), a - b = a + -b) . "try_refl_tac"
• add_left_neg : ∀ (a : α), -a + a = 0
• add_comm : ∀ (a b : α), a + b = b + a
• le : α → α → Prop
• lt : α → α → Prop
• le_refl : ∀ (a : α), a a
• le_trans : ∀ (a b c_1 : α), a bb c_1a c_1
• lt_iff_le_not_le : (∀ (a b : α), a < b a b ¬b a) . "order_laws_tac"
• le_antisymm : ∀ (a b : α), a bb aa = b
• le_total : ∀ (a b : α), a b b a
• decidable_le :
• decidable_eq :
• decidable_lt :
• add_le_add_left : ∀ (a b : α), a b∀ (c_1 : α), c_1 + a c_1 + b

A linearly ordered additive commutative group is an additive commutative group with a linear order in which addition is monotone.

Instances
@[class]
structure linear_ordered_comm_group (α : Type u) :
Type u
• mul : α → α → α
• mul_assoc : ∀ (a b c_1 : α), (a * b) * c_1 = a * b * c_1
• one : α
• one_mul : ∀ (a : α), 1 * a = a
• mul_one : ∀ (a : α), a * 1 = a
• npow : α → α
• npow_zero' : (∀ (x : α), . "try_refl_tac"
• npow_succ' : (∀ (n : ) (x : α), . "try_refl_tac"
• inv : α → α
• div : α → α → α
• div_eq_mul_inv : (∀ (a b : α), a / b = a * b⁻¹) . "try_refl_tac"
• mul_left_inv : ∀ (a : α), a⁻¹ * a = 1
• mul_comm : ∀ (a b : α), a * b = b * a
• le : α → α → Prop
• lt : α → α → Prop
• le_refl : ∀ (a : α), a a
• le_trans : ∀ (a b c_1 : α), a bb c_1a c_1
• lt_iff_le_not_le : (∀ (a b : α), a < b a b ¬b a) . "order_laws_tac"
• le_antisymm : ∀ (a b : α), a bb aa = b
• le_total : ∀ (a b : α), a b b a
• decidable_le :
• decidable_eq :
• decidable_lt :
• mul_le_mul_left : ∀ (a b : α), a b∀ (c_1 : α), c_1 * a c_1 * b

A linearly ordered commutative group is a commutative group with a linear order in which multiplication is monotone.

Instances
@[instance]
@[instance]
@[instance]
@[instance]
def function.injective.linear_ordered_comm_group {α : Type u} {β : Type u_1} [has_one β] [has_mul β] [has_inv β] [has_div β] (f : β → α) (hf : function.injective f) (one : f 1 = 1) (mul : ∀ (x y : β), f (x * y) = (f x) * f y) (inv : ∀ (x : β), f x⁻¹ = (f x)⁻¹) (div : ∀ (x y : β), f (x / y) = f x / f y) :

Pullback a linear_ordered_comm_group under an injective map.

Equations
def function.injective.linear_ordered_add_comm_group {α : Type u} {β : Type u_1} [has_zero β] [has_add β] [has_neg β] [has_sub β] (f : β → α) (hf : function.injective f) (one : f 0 = 0) (mul : ∀ (x y : β), f (x + y) = f x + f y) (inv : ∀ (x : β), f (-x) = -f x) (div : ∀ (x y : β), f (x - y) = f x - f y) :

Pullback a linear_ordered_add_comm_group under an injective map.

theorem linear_ordered_comm_group.mul_lt_mul_left' {α : Type u} (a b : α) (h : a < b) (c : α) :
c * a < c * b
theorem linear_ordered_add_comm_group.add_lt_add_left {α : Type u} (a b : α) (h : a < b) (c : α) :
c + a < c + b
theorem min_neg_neg {α : Type u} (a b : α) :
min (-a) (-b) = -max a b
theorem min_inv_inv' {α : Type u} (a b : α) :
b⁻¹ = (max a b)⁻¹
theorem max_inv_inv' {α : Type u} (a b : α) :
b⁻¹ = (min a b)⁻¹
theorem max_neg_neg {α : Type u} (a b : α) :
max (-a) (-b) = -min a b
theorem min_div_div_right' {α : Type u} (a b c : α) :
min (a / c) (b / c) = min a b / c
theorem min_sub_sub_right {α : Type u} (a b c : α) :
min (a - c) (b - c) = min a b - c
theorem max_div_div_right' {α : Type u} (a b c : α) :
max (a / c) (b / c) = max a b / c
theorem max_sub_sub_right {α : Type u} (a b c : α) :
max (a - c) (b - c) = max a b - c
theorem min_div_div_left' {α : Type u} (a b c : α) :
min (a / b) (a / c) = a / max b c
theorem min_sub_sub_left {α : Type u} (a b c : α) :
min (a - b) (a - c) = a - max b c
theorem max_div_div_left' {α : Type u} (a b c : α) :
max (a / b) (a / c) = a / min b c
theorem max_sub_sub_left {α : Type u} (a b c : α) :
max (a - b) (a - c) = a - min b c
theorem max_zero_sub_eq_self {α : Type u} (a : α) :
max a 0 - max (-a) 0 = a
theorem max_one_div_eq_self' {α : Type u} (a : α) :
max a 1 / 1 = a
theorem eq_zero_of_neg_eq {α : Type u} {a : α} (h : -a = a) :
a = 0
theorem eq_one_of_inv_eq' {α : Type u} {a : α} (h : a⁻¹ = a) :
a = 1
theorem exists_one_lt' {α : Type u} [nontrivial α] :
∃ (a : α), 1 < a
theorem exists_zero_lt {α : Type u} [nontrivial α] :
∃ (a : α), 0 < a
@[instance]
@[instance]
@[instance]
@[instance]
@[simp]
theorem sub_le_sub_flip {α : Type u} {a b : α} :
a - b b - a a b
theorem le_of_forall_pos_le_add {α : Type u} {a b : α} (h : ∀ (ε : α), 0 < εa b + ε) :
a b
theorem le_of_forall_pos_lt_add {α : Type u} {a b : α} (h : ∀ (ε : α), 0 < εa < b + ε) :
a b
def abs {α : Type u} (a : α) :
α

abs a is the absolute value of a.

Equations
theorem abs_of_nonneg {α : Type u} {a : α} (h : 0 a) :
abs a = a
theorem abs_of_pos {α : Type u} {a : α} (h : 0 < a) :
abs a = a
theorem abs_of_nonpos {α : Type u} {a : α} (h : a 0) :
abs a = -a
theorem abs_of_neg {α : Type u} {a : α} (h : a < 0) :
abs a = -a
@[simp]
theorem abs_zero {α : Type u}  :
abs 0 = 0
@[simp]
theorem abs_neg {α : Type u} (a : α) :
abs (-a) = abs a
@[simp]
theorem abs_pos {α : Type u} {a : α} :
0 < abs a a 0
theorem abs_pos_of_pos {α : Type u} {a : α} (h : 0 < a) :
0 < abs a
theorem abs_pos_of_neg {α : Type u} {a : α} (h : a < 0) :
0 < abs a
theorem abs_sub {α : Type u} (a b : α) :
abs (a - b) = abs (b - a)
theorem abs_le' {α : Type u} {a b : α} :
abs a b a b -a b
theorem abs_le {α : Type u} {a b : α} :
abs a b -b a a b
theorem neg_le_of_abs_le {α : Type u} {a b : α} (h : abs a b) :
-b a
theorem le_of_abs_le {α : Type u} {a b : α} (h : abs a b) :
a b
theorem le_abs {α : Type u} {a b : α} :
a abs b a b a -b
theorem le_abs_self {α : Type u} (a : α) :
a abs a
theorem neg_le_abs_self {α : Type u} (a : α) :
-a abs a
theorem abs_nonneg {α : Type u} (a : α) :
0 abs a
@[simp]
theorem abs_abs {α : Type u} (a : α) :
abs (abs a) = abs a
@[simp]
theorem abs_eq_zero {α : Type u} {a : α} :
abs a = 0 a = 0
@[simp]
theorem abs_nonpos_iff {α : Type u} {a : α} :
abs a 0 a = 0
theorem abs_lt {α : Type u} {a b : α} :
abs a < b -b < a a < b
theorem neg_lt_of_abs_lt {α : Type u} {a b : α} (h : abs a < b) :
-b < a
theorem lt_of_abs_lt {α : Type u} {a b : α} (h : abs a < b) :
a < b
theorem lt_abs {α : Type u} {a b : α} :
a < abs b a < b a < -b
theorem max_sub_min_eq_abs' {α : Type u} (a b : α) :
max a b - min a b = abs (a - b)
theorem max_sub_min_eq_abs {α : Type u} (a b : α) :
max a b - min a b = abs (b - a)
theorem abs_add {α : Type u} (a b : α) :
abs (a + b) abs a + abs b
theorem abs_sub_le_iff {α : Type u} {a b c : α} :
abs (a - b) c a - b c b - a c
theorem abs_sub_lt_iff {α : Type u} {a b c : α} :
abs (a - b) < c a - b < c b - a < c
theorem sub_le_of_abs_sub_le_left {α : Type u} {a b c : α} (h : abs (a - b) c) :
b - c a
theorem sub_le_of_abs_sub_le_right {α : Type u} {a b c : α} (h : abs (a - b) c) :
a - c b
theorem sub_lt_of_abs_sub_lt_left {α : Type u} {a b c : α} (h : abs (a - b) < c) :
b - c < a
theorem sub_lt_of_abs_sub_lt_right {α : Type u} {a b c : α} (h : abs (a - b) < c) :
a - c < b
theorem abs_sub_abs_le_abs_sub {α : Type u} (a b : α) :
abs a - abs b abs (a - b)
theorem abs_abs_sub_abs_le_abs_sub {α : Type u} (a b : α) :
abs (abs a - abs b) abs (a - b)
theorem abs_eq {α : Type u} {a b : α} (hb : 0 b) :
abs a = b a = b a = -b
theorem abs_le_max_abs_abs {α : Type u} {a b c : α} (hab : a b) (hbc : b c) :
abs b max (abs a) (abs c)
theorem abs_le_abs {α : Type u} {a b : α} (h₀ : a b) (h₁ : -a b) :
abs a abs b
theorem abs_max_sub_max_le_abs {α : Type u} (a b c : α) :
abs (max a c - max b c) abs (a - b)
theorem eq_of_abs_sub_eq_zero {α : Type u} {a b : α} (h : abs (a - b) = 0) :
a = b
theorem abs_by_cases {α : Type u} (P : α → Prop) {a : α} (h1 : P a) (h2 : P (-a)) :
P (abs a)
theorem abs_sub_le {α : Type u} (a b c : α) :
abs (a - c) abs (a - b) + abs (b - c)
theorem abs_add_three {α : Type u} (a b c : α) :
abs (a + b + c) abs a + abs b + abs c
theorem dist_bdd_within_interval {α : Type u} {a b lb ub : α} (hal : lb a) (hau : a ub) (hbl : lb b) (hbu : b ub) :
abs (a - b) ub - lb
theorem eq_of_abs_sub_nonpos {α : Type u} {a b : α} (h : abs (a - b) 0) :
a = b
@[instance]
@[class]
structure nonneg_add_comm_group (α : Type u_1) :
Type u_1
• add : α → α → α
• add_assoc : ∀ (a b c_1 : α), a + b + c_1 = a + (b + c_1)
• zero : α
• zero_add : ∀ (a : α), 0 + a = a
• add_zero : ∀ (a : α), a + 0 = a
• nsmul : α → α
• nsmul_zero' : (∀ (x : α), . "try_refl_tac"
• nsmul_succ' : (∀ (n : ) (x : α), . "try_refl_tac"
• neg : α → α
• sub : α → α → α
• sub_eq_add_neg : (∀ (a b : α), a - b = a + -b) . "try_refl_tac"
• add_left_neg : ∀ (a : α), -a + a = 0
• add_comm : ∀ (a b : α), a + b = b + a
• nonneg : α → Prop
• pos : α → Prop
• pos_iff : (∀ (a : α), . "order_laws_tac"
• zero_nonneg :
• add_nonneg : ∀ {a b : α},
• nonneg_antisymm : ∀ {a : α},

This is not so much a new structure as a construction mechanism for ordered groups, by specifying only the "positive cone" of the group.

Instances
@[instance]
Equations
theorem nonneg_add_comm_group.nonneg_def {α : Type u} [s : nonneg_add_comm_group α] {a : α} :
theorem nonneg_add_comm_group.pos_def {α : Type u} [s : nonneg_add_comm_group α] {a : α} :
(∀ (a : α), ∀ (a b : α), a b b a
def nonneg_add_comm_group.to_linear_ordered_add_comm_group {α : Type u} [s : nonneg_add_comm_group α] (nonneg_total : ∀ (a : α), ) :

A nonneg_add_comm_group is a linear_ordered_add_comm_group if nonneg is total and decidable.

Equations
@[instance]
def order_dual.ordered_add_comm_group {α : Type u}  :
Equations
@[instance]
Equations
@[instance]
def prod.ordered_comm_group {G : Type u_1} {H : Type u_2}  :
Equations
@[instance]
def prod.ordered_add_comm_group {G : Type u_1} {H : Type u_2}  :
@[instance]
def multiplicative.ordered_comm_group {α : Type u}  :
Equations
@[instance]